CHALLENGES OF INDUSTRIAL COOPERATION IN THE EAEU COUNTRIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the trends and challenges in the development of industrial cooperation among the member states of the Eurasian Economic Union (EAEU) under the conditions of digital transformation, intensified sanctions pressure, and changes in global trade flows. Industrial cooperation is identified as a key instrument for ensuring economic resilience, technological sovereignty, and integrative interaction among the economies of Armenia, Belarus, Kazakhstan, Kyrgyzstan, and Russia. The theoretical framework is based on the principles of international trade theory, economic integration, and innovation management. The study applies comparative, systemic, and statistical methods, as well as official documents of the Eurasian Economic Commission (EEC) and the Eurasian Intergovernmental Council, including Decisions No. 5 (2021) and No. 3 (2023). The results show that the EAEU is forming a network-based model of industrial integration that unites production, technological, and financial capacities. Priority areas of cooperation include mechanical engineering, metallurgy, the chemical and light industries, energy, and digital manufacturing. The effectiveness of cooperation depends on the level of digitalization and the coordination of industrial policies. The study identifies several constraints: fragmentation of production chains, differences in technical standards, uneven digital maturity, and limited access of small and medium-sized enterprises (SMEs) to financing. Additional challenges arise from Western sanctions and the U.S. tariff policy toward China, which highlight the growing strategic partnership between the EAEU and the People’s Republic of China. For the Kyrgyz Republic, participation in EAEU industrial cooperation and infrastructure development with China create new opportunities for industrial modernization, digital transformation, and export growth.
Keywords: EAEU, industrial cooperation, digital economy, sanctions, Kyrgyzstan, China, integration.